The Mechanisms of Cognitive Metaphor Functioning from the Perspective of George Lakoff and Gilles Fauconnier - Abdeldayem, Abdelrahman (El Omda in Linguistics and Discourse Analysis, 2020)
The attention of customary linguistics has moved towards metaphors and metaphor because it ended with theorists of language and gratitude to recognize that the understanding of linguistic language and abilities is not complete without a clear representation of metaphor. This study, entitled “ Mechanisms of customary metaphor from the perspective of Lycov and Fukuniyi” seeks to investigate the mechanisms of customary metaphor from the perspective of the two words, Lycov and Fukuniyi, by indentifying their types of metaphor, the experimental dimensions of metaphor, and how metaphor works.